Capital Structure and Financial Performance of Manufacturing Companies in Indonesia - Ni Luh Ira Suitri; Mohamad Agus Salim Monoarfa; Srie Isnawaty Pakaya (Universitas Negeri Gorontalo, 2021)
This study aims to determine whether the Capital Structure affects the financial performances partially and simultaneouslly. The Capital Structure in this study is proxide by Debt to Asset Ratio (DAR) and Long Term Debt to Equity Ratio (LTDER), whereas the financial performance is proxide by Return On Asset (ROA). the type of data used in this study is secondary data obtained from the financial statements os plastic and packaging companies listed on the Indonesia Stock Exchange in 2012-2019. The analysis method uses multiple linier regression analysis. The result revealed that partially DAR had negative and significant effect on ROA, while LTDER had no significant effect on ROA. The result also shows that simultaneouslly DAR and LTDER have a significant effect on ROA.